GROWTH AND SURVIVAL IN THE FOOD OF JUVENILE Osteoglossum bicirrhosum - FERNÁNDEZ MÉNDEZ, Christian (2019)
The main objective of this study was to evaluate the effect of three foods on the growth and survival of juveniles of arahuana Osteoglossum bicirrhosum. 81 specimens (6.5 ± 0.36 cm and 1.03 ± 0.03 g) were used and distributed in aquariums with 15 L of water at a density of 0.6 fish L-1. Three foods were used: commercial feed, chironomids Chironomus sp. and live specimens of Poecilia reticulata, with three replicas distributed in a completely randomized design (CRD) for 30 days. The results show that fish fed with chironomids and balanced feed obtained a significant performance (p <0.05) in weight, specific growth rate, relative growth rate and condition factor compared to juveniles fed live fish. However, no significant differences (p> 0.05) in total length and survival were found in the different feeding treatments. In conclusion, the use of chironomids and balanced food show a better performance in weight growth and condition factor in juveniles of arahuana O. bicirrhosum.